White matter hyperintensities and risks of cognitive impairment and dementia: A systematic review and meta-analysis of 36 prospective studies - Hu, He-Ying; Ou, Ya-Nan; Shen, Xue-Ning; Qu, Yi; Ma, Ya-Hui; Wang, Zuo-Teng; Dong, Qiang; Tan, Lan; Yu, Jin-Tai (Neuroscience and biobehavioral reviews, 2021)
•WMHs conferred a 14 % elevated risk of cognitive impairment and ACD.•WMHs increased both AD risk and VaD risk.•Periventricular WMH were related with increased risk of ACD.•The dose-response analysis showed a nonlinear association between WMHs and ACD. White matter hyperintensities of presumed vascular origin (WMH) are one of the imaging features of cerebral small vessel disease. Controversies persist about the effects of WMH on cognitive dysfunction. This meta-analysis aimed to identify the associations of WMH with risks of cognitive impairment and dementia. We searched PubMed, EMBASE and Cochrane Library for prospective studies. Primary analyses of cognitive dysfunction and sub-analyses of specific outcomes and study characteristics were conducted using random-effect models. Thirty-six prospective studies with 19,040 participants were included. WMH at baseline conferred a 14 % elevated risk of cognitive impairment and all-cause dementia (ACD). WMH also conferred 25 % elevated risk of Alzheimer’s disease and 73 % elevated risk of vascular dementia. Risk effects of high-grade WMH and continually increasing WMH (in volume or severity) on ACD were revealed. Periventricular WMH conferred a 1.51-fold excess risk for dementia. WMH were associated with increased risk of cognitive dysfunction and could become a neuroimaging indicator of dementia.